Sửa lại đề nha:
\(\dfrac{1}{x^2+9x+12}thành\dfrac{1}{x^2+9x+20}\)
⇔ \(\dfrac{1}{\left(x+2\right)\left(x+3\right)}+\dfrac{1}{\left(x+3\right)\left(x+4\right)}+\dfrac{1}{\left(x+4\right)\left(x+5\right)}+\dfrac{1}{\left(x+5\right)\left(x+6\right)}=\dfrac{1}{8}\)
⇔ \(\dfrac{1}{x+2}-\dfrac{1}{x+3}+\dfrac{1}{x+3}-\dfrac{1}{x+4}+\dfrac{1}{x+4}-\dfrac{1}{x+5}+\dfrac{1}{x+5}-\dfrac{1}{x+6}=\dfrac{1}{8}\)
⇔ \(\dfrac{1}{x+2}-\dfrac{1}{x+6}=\dfrac{1}{8}\)
⇔ \(\dfrac{x+6-x-2}{\left(x+2\right)\left(x+6\right)}=\dfrac{1}{8}\)
⇔ \(\dfrac{4}{x^2+8x+12}=\dfrac{1}{8}\)
⇔ \(x^2+8x+12=32\)
⇔ \(x^2+8x-20=0\)
⇔ \(\left(x-2\right)\left(x+10\right)=0\)
⇔ \(\left[{}\begin{matrix}x=2\\x=-10\end{matrix}\right.\)